Primary Burkitt Lymphoma of the Chest Wall - Rommel Lu (Case Reports in Hematology)
Burkitt lymphoma (BL) originating in the skin and soft tissue at any site is exceedingly rare. This paper is about a case of primary sporadic BL that presented as an isolated, rapidly enlarging chest wall mass arising from skin and/or soft tissue in an adult. As with other BL presentations, this patient was treated with aggressive chemotherapy with central nervous system (CNS) chemoprophylaxis, but he later died because of sepsis.